Association between diabetic retinopathy and incident cognitive impairment. Issue 11 (30th January 2019) - Gupta, Preeti; Gan, Alfred Tau Liang; Man, Ryan Eyn Kidd; Fenwick, Eva K; Sabanayagam, Charumathi; Mitchell, Paul; Cheung, Carol Y; Cheung, Ning; Wong, Tien Yin; Cheng, Ching-Yu; Lamoureux, Ecosse Luc
Abstract : Background/Aim: The relationship between diabetic retinopathy (DR) and cognitive impairment (CI) is unclear due to equivocal findings from cross-sectional studies and a lack of long-term data. In this population-based cohort study, we investigated the longitudinal association between the severity of DR and the incidence of CI. Methods: 682 participants with diabetes, gradable retinal photographs and no CI at baseline 2004–2011) and complete relevant data at follow-up 2010–2016 from the Singapore Epidemiology of Eye Disease Study were included. CI was assessed using the validated Abbreviated Mental Test (AMT), defined as scores of ≤6 and ≤8 for those with 0–6 and >6 years of formal education, respectively. Six-year incident CI was defined as having no CI at baseline but present at the follow-up visit. Results: Of the 682 included participants, 483 (70.8%) had no DR and 199 (29.2%) had any DR. Of those with DR, 142 (20.8%) had minimal/mild DR and 57 (8.4%) had moderate or worse DR at baseline. At the follow-up visit, 40 (5.9%) participants had incident CI based on AMT. In multivariate analysis compared with participants without DR, those with any DR had more than twofold increased odds of incident CI (OR (95% CI): 2.32 (1.07 to 5.03)). Participants with moderate or worse DR had threefold increased odds of developing CI (3.41 (1.06 to 11.00)), compared with those with no DR. Conclusions: DR, particularly at the more severe stages, is associated with increased risk of developing CI, independent of vision and other risk factors.